2014
DOI: 10.1080/13636820.2014.983957
|View full text |Cite
|
Sign up to set email alerts
|

Project-based vocational education and training: opportunities for teacher guidance in a Swedish upper secondary school

Abstract: Project-based vocational education and training (PBVET) is a way to conduct vocational education in Swedish construction programmes. The educational settings used include projects ranging from minor construction to advanced houses. Due to limited research on this kind of educational setting, it is important to further develop knowledge on affordances in a PBVET. The aim of this study is to describe and analyse teachers' perception on opportunities for teacher guidance provided in a PBVET. From this broad aim, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…In a study comparing the training of nurses and IT technicians, Ümarik et al (2010) found several problems in assessment practices, including "fictitious assessment practices, low quality of training and motivation of workplace trainers, and also the lack of correspondence between the school curriculum and the competence base needed in the real workplace" (p. 145). Problem-based learning in vocational education and training (PBVET) was seen to have a positive impact on competency development in the field of building construction (Fjellström, 2015). Ogbuanya and Chukwuedo (2017) implemented "varieties of faulty mobile phones ranging from simple or budget phones to high technology phones such as smart phones" in an IT technician programme, and in some cases, "faults were deliberately induced in the phones to enable the students to acquire varieties of skills during the training sessions" (p. 103).…”
Section: Constructing Knowledge Through Practicementioning
confidence: 99%
“…In a study comparing the training of nurses and IT technicians, Ümarik et al (2010) found several problems in assessment practices, including "fictitious assessment practices, low quality of training and motivation of workplace trainers, and also the lack of correspondence between the school curriculum and the competence base needed in the real workplace" (p. 145). Problem-based learning in vocational education and training (PBVET) was seen to have a positive impact on competency development in the field of building construction (Fjellström, 2015). Ogbuanya and Chukwuedo (2017) implemented "varieties of faulty mobile phones ranging from simple or budget phones to high technology phones such as smart phones" in an IT technician programme, and in some cases, "faults were deliberately induced in the phones to enable the students to acquire varieties of skills during the training sessions" (p. 103).…”
Section: Constructing Knowledge Through Practicementioning
confidence: 99%
“…Since feedback in workplaces or school workshops originates from the need to adhere to and uphold certain levels of quality and speed, verbal feedback is often clear-cut and straightforward "telling". However, telling may also include contradictory teacher messages from a student's perspective, e.g., exhortation to solve a problem independently rather than with a teacher's help or to re-do tasks rather than offering support during work, as observed for example in a Swedish building construction programme (Fjellström, 2014).…”
Section: Studies Of Modes Of Feedbackmentioning
confidence: 99%
“…In contrast, in another workshop setting, a different apprentice encountered sarcastic comments while getting in the crossfire between two competing messages from his supervisor and another worker (cf. Fjellström, 2014). Application of methodology from "various fields of linguistics" (Fillieattaz, 2011, p. 490) reportedly enabled a fine-grained interactional perspective, describing how feedback (as telling) in distributed guidance can both enhance and hinder learning in workplaces.…”
Section: Studies Of Modes Of Feedbackmentioning
confidence: 99%
“…The apprentices addressed in this article had all completed a VET programme in order to become a woodworker in the construction industry. They were selected on the basis of having participated in the first part of this research project (Fjellström 2014(Fjellström , 2015. Based on the overall aim and purpose of this study, former students who did not proceed to apprenticeship were excluded, which reduced the number of participating apprentices from 15 to 11.…”
Section: Methodsmentioning
confidence: 99%